‘How many miles doth your hand travell!’: Women’s textual journeys in seventeenth-century England - Kaznowska, H (2018)
The seventeenth century is often called the first truly global era, but worldly adventures did not require physical movement abroad. Despite the limitations placed on women’s physical movement that were prevalent in early modern English culture, their textual habits reveal global curiosity. My thesis uncovers the ways in which some English women, many of whom had neither the means nor opportunity to travel, experienced this era of exploration through their own reading and writing. By recognising cases of virtual travel, as well as the numerous ways of interpreting and influencing the foreign, this study introduces an often-overlooked yet vital discourse concerning imagined travels. When it comes to women’s recorded experiences of the world beyond their own, scholarship has tended to focus on individual female writers who physically travelled abroad, and their creation of some kind of travelogue. Unless we consider the varied and frequent series of exchanges between English travellers and women at home in England, I argue, we ignore the complexly gendered transnational dialogues negotiating global information. Women left textual traces of their worldly journeys across print and manuscript – including, but not limited to, sermons, poems, conduct literature, almanacs, petitions, wage receipts, powers of attorney, commonplace books, letters, and diaries. I consider examples of each mode to see how genres were specifically chosen to cater to the author’s purpose and intended audience, as well as being inextricably connected to their social position and levels of education. My thesis therefore advances the study of non-elite women’s literary and historical resources, most of which have not received sufficient scholarly attention. I explore the processes of piecing together stories through sometimes fragmented or anecdotal sources, considering how we might interpret the signs that are left, which are often slight when dealing with this demographic. To speak of these engaged women helps to further our understanding of how travel is a multi-faceted concept, and stimulates new ways of thinking about women’s textual contributions during a period of profound global discoveries.